SEMIOTIKA LABA AKUNTANSI: STUDI KRITIKAL-POSMODERNIS DERRIDEAN - Riduwan, Akhmad; Triyuwono, Iwan; Irianto, Gugus; Ludigdo, Unti (UI Scholars Hub, 2010)
The main aims of the research are (a) to understand the interpretation of accounting earnings by accountants and non-accountants; and (b) to perform a deconstructively semiotics-reading about the text related with their interpretations of accounting earnings. This research is performed based on the critical-postmodern approach, especially based on the Jacques Derrida s philosophy. Based on the Jacques Derrida s philosophy, deconstructive semiotics analysis expresses some realities that are (a) accounting earnings are traces, either the trace as a history of text or as an experience and interest of interpreter; (b) nothing outside the text of accounting earnings because the meanings of accounting earnings are intertextual, accounting earnings are the result of simulation only, and the meanings of accounting earnings do not exceed the experience and interest of interpreter; (c) accounting earnings are the metaphysics of presence, in the means of